Irish Influence in the Consonantal Spellings of Old English - David L. White (Anglica. An International Journal of English Studies)
The consonantal spellings of Old English (OE) were significantly influenced by the consonantal spellings of Old Irish (OI). 1) <th/þ> vs. (post-vocalic) <d/ð>: though OE did not have a distinction between /θ/ and /ð/, OI did, spelling this as vs. (postvocalic) <d>. 2) <h> vs. <ch>: though OE did not have a distinction between /h/ and /x/, OI did, spelling the latter as <ch>. 3) <ch> and : both spellings appear to be from Irish. 4) <cg>: spellings of the “mixed voice” type, including “cg”, occur in OI, where they can spell either single or geminate voiced plosives. 5) <bb> (and <cg>): almost certainly in fi nal position <bb, cg> in OE represent singles, not geminates, as they can in OI. 6) Spelling rules referring to post-vocalic position: all cases show OE spelling having had, like OI spelling, rules referring to post-vocalic position, which appear to be additionally evidenced by “illogical doubling” in Northumbrian. 7) The meaning of <g> before front Vs: in OE spelling as in OI spelling, but not as in Roman Latin spelling, <g> before front Vs spells a palatal approximant rather than a palatal affricate. The overall conclusion is that the OE spelling system was developed by Irish missionary linguists.